The Slowness From Latent Aspects to Relevant Agency (EAAE Annual Conference Proceedings, 2019)
Most of the artificial assembly that surrounds us is made through a series of processes, and the finalised objects emerge from an operation of multitude of devices. Since each space carries with it something of the being that designed it, every artefact hides some technical invention. The general trend of market uniformity, technological mass, and a constant flow of materials that stimulate our senses, reduces our ability to consider alternatives and possible deviations from the omnipresent. One of the potentials of education is to slow down the process and draw our attention to a material world. Material world itself can be considered from two sides: as a structural matter or as a conceptual strategy. In such a way, the material character of architecture and concentration on the matter becomes a substantive medium of design.
Keywords: assignment; substance; technique; awareness; alternative